Tactical Public Relation dalam Mengembangkan Citra Destination Wisata Kota Padang - Neni Efrita (Universitas Islam Negeri Imam Bonjol Padang, 2015)
Public Relations (PR) is an activity that aims to gain the trust, mutual understanding and a good image of the public. The existence of PR is to develop a positive image of the institution / organization and tourist destination. Every tourist destination is always trying to strengthen a positive image in the view of the international market. It is necessary for PR tactics in developing tourist destination image including the city of Padang in West Sumatera. Tactics of Tourism and Culture Public Relation of Padang offer promises in developing the image of a tourist destination begins with: determining the programs and activities, setting objectives and results, the selecting the targeted audience, developing messages, identifying the messenger and determining the mechanism of communications/ media. To determine the promotion programs which, it was established a work unit officials of commitments makers working in formulating the objectives and communication mechanism activities such as determining media to promote including printed media, electronic, internet and even exhibition/ expo local and international media. PR’s tactics gives evidence in developing the image of the tourist destination city of Padang by using a third person as a mouthpiece in delivery the programs that have been planned by inviting journalists, writers or public opinion, whose activities can be seen in www.padangtourism.info. Travel agents, journalists of mass media, public figures and visitors can also form a positive or negative image of the tourist destination of public facilities such as the first cache of airport, terminal and railway station